Sustainable food security for all by 2020: proceedings of an international conference - International Food Policy Research Institute (International Food Policy Research Institute, 2002)
In 1995, the International Food Policy Research Institute’s (IFPRI’s) 2020 Vision for Food, Agriculture, and the Environment Initiative held its first international conference, which articulated a global vision for eliminating food insecurity. Since then, profound developments have occurred with extraordinary implications for global food security prospects, compelling IFPRI and its 2020 Vision Initiative to hold a second conference, entitled “Sustainable Food Security for All by 2020,” in Bonn, Germany, on September 4– 6, 2001. The ultimate objective of the Conference was to influence and catalyze action by key actors—including governments, international aid agencies, nongovernmental organizations, business and industry, and media — to achieve sustainable food security for all by 2020. Over 900 individuals from 71 countries participated in the Conference. One-quarter of the participants were from developing countries, and 40 percent were female. A wide variety of stakeholders came together — one-quarter of the participants were from nongovernmental organizations, one-fifth from government, one-tenth from media, and just over one-twentieth from business and industry. In addition, the Conference attracted very senior policymakers. The Conference began by taking stock of the current situation and prospects for the future. The second part, or heart, of the Conference focused on four key emerging forces: (i) demographic, health, and nutrition forces; (ii) economic forces; (iii) technological and environmental forces; and (iv) sociopolitical forces (see Appendix 1 for Conference program). The third and final part built on the action items identified in the previous sessions but focused on the larger issues of setting the priorities for action and identifying the roles and responsibilities of key actors. This proceedings volume compiles the presentations made by the 73 speakers and chairs (see Appendix 2 for biographical notes) and synthesizes the discussions held throughout the three days. Note that these presentations have been transcribed and lightly edited. All speakers and chairs were invited to submit written summary notes for distribution during the Conference.....Several auxiliary activities complemented the Conference program, highlights of which are included in this volume. Poster and essay competitions invited young people from around the world to share in pictures and in words how they saw our world in 2020. Throughout the Conference, an electronic voting system quickly gauged the participants’ views on key topics, subsequently catalyzing debates and discussions. An African artist was commissioned to create comic strips depicting his perspective on relevant topics.